Use of vaccines to fight brucellosis in animals - Nandi, S; Chander, Vishal; Yadav, Jeet Singh (Indian Farming, 2016)
Brucellosis is a complicated bacterial disease affecting a number of animal species and considered as a reemerging zoonosis. It is prevalent in most of the countries in the world except 17 countries which are free from bovine brucellosis. A number of vaccines are available namely B. abortus strain 19, B. melitensis Rev 1, B. abortus strain 45/20, B. abortus RB 51 and BS2 vaccine for use in animals in controlling brucellosis. However, each one has its own advantages and disadvantages. No one provides 100% protection against challenge with Brucella organisms. However, judicial use of the different vaccines in the herd offers an advantage to reduce the incidence of the disease and which in turn helps in controlling and ultimately eradicate the disease in animals. With the control of the disease in animals, the incidence of disease in humans will also be reduced.